Korean woman in context: its historical role and the resurgence of feminist movements in the non-silence generation - López Rocha, Nayelli (2023)
The concept of contemporary Korean women is a big question mark for other societies. The images projected by cultural industry in full swing worldwide, contrast strongly with the experiences that are lived by women in the Asian country in focus. Confronted with the Confucianism heritage that permeates society, Korean women are at a generational crossroads. The youngest, having accessed education that provided them with tools to question the social system, shake the mandates historically inherited by a socially reproduced gender system. With the technologization and global information flows, local mindset is confronted with other realities, allowing the young women to position their collective vision, questioning the patriarchal and anthropocentric system reflected in the State itself. To meet social demands and guarantee the security, development and participation of women, the State must appeal to an equitable system without infringing them in a society that is self-cataloged as democratic.